Massive Lingual and Sublingual Haematoma following Postextractive Flapless Implant Placement in the Anterior Mandible - Luisa Limongelli; Angela Tempesta; Vito Crincoli; Gianfranco Favia (Case Reports in Dentistry)
Dental implants placement in the anterior mandible with flap or flapless technique is a routine procedure and is considered to be safe. However, serious life-threatening complications may occur. We report the first case of massive lingual and sublingual haematoma following postextractive implant placement in the anterior mandible with flapless technique. A 45-year-old female patient underwent placement of four immediately postextractive implants in the anterior mandible using flapless technique. During the procedure, the patient referred intense acute pain and worsening sign of airway obstruction, dysphagia, dyspnea, and speech difficulties. Bimanual compression of the mouth floor, lingual surface of the mandible, and submental skin was maintained for approximately 25 minutes in order to stop the bleeding. Computerized tomography highlighted the massive lingual and sublingual haematoma. The symptoms and signs had almost completely resolved in the next 48 hours. The prevention of these complications is mandatory with clinical and CT analyses, in order to highlight mandibular atrophy and to select carefully the correct length and angulation of bone drilling and to keep more attention to the flapless technique considering the elevation of a lingual mucoperiosteal flap to access the mandibular contour intraoperatively and to protect the sublingual soft tissues and vasculature in high risk cases.